Accessibility: Distribution across diverse populations - Kristin Carlson; Andrew Owen (Journal of Transport and Land Use)
High-resolution data are used to evaluate the distribution of job accessibility among workers at the national, state, regional, and urban scales. Annually updated accessibility datasets produced by the National Accessibility Evaluation are paired with Census data to tie accessibility, jobs, and worker information at the block level. Minnesota is selected as a case study for analyzing accessibility and drawing findings from the spatial datasets. The average accessibility by worker age, monthly earnings, educational attainment, race, and sex are calculated using data for the weekday morning commute by automobile and transit. The greatest variation in average accessibility among demographic groups is found for worker race. Based on home location, non-White workers systematically experience far higher accessibility to jobs by both automobile and transit than White workers as a percent difference from the population average. The finding holds at the national, state, and regional geographies. Additional findings are presented for each demographic group. The analyses presented here can be applied to other states and regions to identify where accessibility is distributed most and least equitably.